Pengaruh Corporate Social Responsibility, Capital Intensity dan Profitabilitas Terhadap Penghindaran Pajak pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2019 – 2022 - Vina Puspitawati; Lihan Rini Puspo Wijaya; Irawan Irawan (Jurnal Riset Akuntansi, 2025)
This research uses quantitativee methods involving a sample of 34 manufacturing companies listed on the IDX in 2019-2022. Manufacturing companies listed on the IDX in 2019-2022. The data taken is secondary data related to manufacturing company reports for the 2019-2022 period. Data collection uses the documentation method by collecting company financial reports and also the company's annual report. Data analysis using multiple linear regression. The results showed that Corporate Social Responsibility affects tax avoidance, Capital Intensity affects tax avoidance, and Profitability proxied by the ROA parameter affects tax avoidance.